2016
DOI: 10.1371/journal.pone.0154864
|View full text |Cite
|
Sign up to set email alerts
|

Human Bacterial Artificial Chromosome (BAC) Transgenesis Fully Rescues Noradrenergic Function in Dopamine β-Hydroxylase Knockout Mice

Abstract: Dopamine β-hydroxylase (DBH) converts dopamine (DA) to norepinephrine (NE) in noradrenergic/adrenergic cells. DBH deficiency prevents NE production and causes sympathetic failure, hypotension and ptosis in humans and mice; DBH knockout (Dbh -/-) mice reveal other NE deficiency phenotypes including embryonic lethality, delayed growth, and behavioral defects. Furthermore, a single nucleotide polymorphism (SNP) in the human DBH gene promoter (-970C>T; rs1611115) is associated with variation in serum DBH activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 48 publications
2
8
0
Order By: Relevance
“…We found that over the course of 1 h, NE-deficient mice exhibited reduced locomotor activity and more rapid habituation in the novel test environment compared to control mice. These findings are congruent with previous reports from our lab and suggest that novelty may have reduced incentive value or intrinsic salience in NE-deficient animals (Cubells et al 2016;Porter-Stransky et al 2019;Weinshenker et al 2002a). Importantly, novel environments elicit an initial increase in locomotion in Dbh -/-mice that habituates over time, suggesting that spatial memory mechanisms that distinguish novel and familiar environments remain intact in the absence of NE.…”
Section: Norepinephrine Is Required For Sustained Locomotor Activatiosupporting
confidence: 93%
See 1 more Smart Citation
“…We found that over the course of 1 h, NE-deficient mice exhibited reduced locomotor activity and more rapid habituation in the novel test environment compared to control mice. These findings are congruent with previous reports from our lab and suggest that novelty may have reduced incentive value or intrinsic salience in NE-deficient animals (Cubells et al 2016;Porter-Stransky et al 2019;Weinshenker et al 2002a). Importantly, novel environments elicit an initial increase in locomotion in Dbh -/-mice that habituates over time, suggesting that spatial memory mechanisms that distinguish novel and familiar environments remain intact in the absence of NE.…”
Section: Norepinephrine Is Required For Sustained Locomotor Activatiosupporting
confidence: 93%
“…In the NIL test, high locomotor reactivity to novelty is interpreted as increased exploratory behavior, while low locomotor responses are interpreted as decreased exploratory behavior (Cubells et al 2016;Schroeder et al 2013;Stone et al 1999). Neophobia can be assessed in mice with the novelty-suppressed feeding (NSF) test, a conflict-based model of anxiety-like behavior in which anxiety elicited by exposure to an unfamiliar environment suppresses feeding in hungry mice presented with food (Cryan and Sweeney 2011;Dulawa et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Each mouse was placed in a clear, Plexiglas chamber contained within a chemical fume hood, and flurothyl was introduced into the chamber (20 μl/min) such that it vaporized and filled the chamber. Latencies to the first myoclonic jerk and generalized tonic-clonic seizure (GTCS) were recorded 33; 34 Mice were removed from the chamber immediately after the GTCS.…”
Section: Methodsmentioning
confidence: 99%
“…Exclusive anatomic targeting of tau fibrils to the LC is technically very challenging due to the small size of this nucleus (1500 neurons in a rodent), and there is no way to ensure noradrenergic neuron specificity. By contrast, genetic strategies have been successful in targeting LC neurons to produce effector and reporter proteins with cell-type specificity through promoter-driven expression using NE synthesis enzymes (TH, DBH) [ 81 83 ], LC transcription factors (Phox2b) [ 84 , 85 ], and LC specification genes (Ear2 and DBH/En1) [ 36 , 86 , 87 ]. Recent work has shown selective and robust viral-mediated expression using Phox2b-dependent promoters [ 84 , 85 ], Cre-dependent expression in TH-Cre mice [ 81 , 88 ], or microinjections of virus containing a constitutive promoter [ 89 ].…”
Section: In Vivo Models Of Tau Spreadmentioning
confidence: 99%